Production of active Exendin-4 in Nicotiana benthamiana and its application in treatment of type-2 diabetics - Akter, Shammi; Afrin, Shajia; Kim, Jaeyoon; Kang, Joohyun; Razzak, Md Abdur; Berggren, Per-Olof; Hwang, Inhwan (Frontiers in Plant Science, 2022)
GLP-1 (Glucagon-like peptide-1) is a peptide that stimulates insulin secretion from the β-cell for glycemic control of the plasma blood glucose level. Its mimetic exenatide (synthetic Exendin-4) with a longer half-life of approximately 3.3–4 h is widely used in clinical application to treat diabetes. Currently, exenatide is chemically synthesized. In this study, we report that the GLP-1 analogue recombinant Exendin-4 (Exdn-4) can be produced at a high level in Nicotiana benthamiana, with an estimated yield of 50.0 µg/g fresh biomass. For high-level expression, we generated a recombinant gene, B:GB1:ddCBD1m:8xHis:Exendin-4 (BGC:Exdn-4), for the production of Exendin-4 using various domains such as the BiP signal peptide, the GB1 domain (B1 domain of streptococcal G protein), a double cellulose binding domain 1 (CBD1), and 8 His residues (8xHis) to the N-terminus of Exendin-4. GB1 was used to increase the expression, whereas double CBD1 and 8xHis were included as affinity tags for easy purification using MCC beads and Ni2+-NTA resin, respectively. BGC:Exdn-4 was purified by single-step purification to near homogeneity using both Ni2+-NTA resin and microcrystalline cellulose (MCC) beads. Moreover, Exdn-4 without any extra residues was produced from BGC:Exdn-4 bound onto MCC beads by treating with enterokinase. Plant-produced Exdn-4 (Exendin-4) was as effective as chemically synthesized Exendin-4 in glucose-induced insulin secretion (GIIS) from mouse MIN6m9 cells a pancreatic beta cell line.